2018
DOI: 10.1111/jai.13743
|View full text |Cite
|
Sign up to set email alerts
|

Does body size affect the response to exercise in shortnose sturgeon (Acipenser brevirostrum)?

Abstract: The effect of body size on various hematological variables was examined in juvenile shortnose sturgeon (Acipenser brevirostrum) ranging in mass from 38 to 730 g. The blood was examined for differences in plasma ionic composition (Na + , K + , Cl − ), blood oxygen carrying capacities (hemoglobin, hematocrit), and plasma metabolite concentrations (lactate, glucose), before and following a standard 5-min chasing stress. All measured resting hematological variables were size independent in shortnose sturgeon. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Hypoxia and exercise stressors can trigger the fish to increase lactate as a result of the anaerobic metabolism (Rodnick & Planas, 2016; Sheng et al, 2019). Lactate levels show different values in fish species after the stress (Brown & Kieffer, 2019; Eslamloo & Falahatkar, 2014; Jafari & Falahatkar, 2019; Kieffer et al, 2001) which is reflected in species‐specific pattern and different methods for measurement (Fanouraki et al, 2011; Kieffer et al, 2001). The results revealed an increase in lactate levels up to 1 h that reflected increase of anaerobic activity of white muscle and metabolic rate through the periods of severe exercise (Pankhurst & Dedualj, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia and exercise stressors can trigger the fish to increase lactate as a result of the anaerobic metabolism (Rodnick & Planas, 2016; Sheng et al, 2019). Lactate levels show different values in fish species after the stress (Brown & Kieffer, 2019; Eslamloo & Falahatkar, 2014; Jafari & Falahatkar, 2019; Kieffer et al, 2001) which is reflected in species‐specific pattern and different methods for measurement (Fanouraki et al, 2011; Kieffer et al, 2001). The results revealed an increase in lactate levels up to 1 h that reflected increase of anaerobic activity of white muscle and metabolic rate through the periods of severe exercise (Pankhurst & Dedualj, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…() have shown that the post‐exercise metabolic rate increases only 2‐fold following 5 min of exhaustive exercise in juvenile shortnose and Atlantic sturgeon. Post‐exercise plasma lactate and cortisol levels in juvenile shortnose sturgeon typically are low relative to teleosts (Baker et al ., ; Brown & Kieffer, ), and muscle energy reserves (PCr, glycogen) and lactate levels do not change substantially following exhaustive exercise (Kieffer et al ., ). The fact that the physiological response to exercise is muted and the time for post‐exercise recovery occurs quickly in juvenile shortnose sturgeon (Kieffer et al ., ; Zhang & Kieffer, ) may enhance their ability for repeated exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The second and third cycles included a 360 s flushing period followed by 60 s for appropriate mixing and a final 300 s period of measurement. Varying durations in the measurement period have been used to assess MMR post‐exercise in larval and juvenile fish (Norin & Clark, 2016; Zhang et al ., 2019) and recently it was suggested that a shorter time period be used in shortnose sturgeon to gain a more accurate reflection of MMR (Brown and Kieffer 2019). Thus, we calculated MMR in the 20–22 and 129–130 dph age groups using oxygen declines within the chamber of 1% and 2% or 1%, 2% and 5% post‐exhaustive exercise, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Much of our understanding of the relationship between ṀO 2 and activity has focused on juvenile or adult fish, and most of the method development for measurement of ṀO 2 has been conducted on teleosts, with few studies establishing appropriate methodology in nonteleostean larval fishes. In comparison to teleosts, acipenseriforms (sturgeon and paddlefish) are thought to have a dampened physiological response to exercise protocols (Baker et al ., 2005; Brown & Kieffer, 2019), which would influence estimation of SMR and MMR. For example, lake sturgeon are known to have a lower ratio of anaerobic capacity in lactate dehydrogenase to citrate synthase in red muscle and heart compared to teleosts (Singer et al ., 1990).…”
Section: Introductionmentioning
confidence: 99%